2022
DOI: 10.1108/maj-07-2021-3225
|View full text |Cite
|
Sign up to set email alerts
|

Key audit risks and audit procedures during the initial year of the COVID-19 pandemic: an analysis of audit reports 2019-2020

Abstract: Purpose The purpose of this study is to explore audit procedure disclosures related to key audit risks, during the prior year and the initial year of the COVID-19 outbreak, by reporting on matters published in over 3,000 Australian statutory audit reports during 2019 and 2020. Design/methodology/approach This study partially uses latent semantic analysis methods to apply textual and readability analyses to external audit reports in Australia. The authors measure the tone of the audit reports using the Loughr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
57
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 45 publications
6
57
3
Order By: Relevance
“…As COVID-19 outbreak continues to create disruptions to businesses and public accounting firms, our study provides an implication for auditors and client firms to address the pandemic challenges by quickly adapting to the evolving financial reporting and audit landscape. Using a sample of Australian audit reports, Kend and Nguyen (2022) find that smaller accounting firms use fewer audit procedures related to COVID-19 audit risk than larger accounting firms during the pandemic. Their finding may suggest that a significant segment of the accounting/auditing industry has not done enough to adjust to the pandemic challenges that accounting firms are facing.…”
Section: Conclusion and Future Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…As COVID-19 outbreak continues to create disruptions to businesses and public accounting firms, our study provides an implication for auditors and client firms to address the pandemic challenges by quickly adapting to the evolving financial reporting and audit landscape. Using a sample of Australian audit reports, Kend and Nguyen (2022) find that smaller accounting firms use fewer audit procedures related to COVID-19 audit risk than larger accounting firms during the pandemic. Their finding may suggest that a significant segment of the accounting/auditing industry has not done enough to adjust to the pandemic challenges that accounting firms are facing.…”
Section: Conclusion and Future Studiesmentioning
confidence: 99%
“…Literature examining external audits during COVID-19 is growing. However, existing studies use a secondary approach (Albitar et al , 2021; Hay et al , 2021), interviews (Alderman, 2021; Castka and Searcy, 2021; Luo and Malsch, 2020), surveys (Eulerich, 2021; Heltzer and Mindak, 2021) and textual analysis (Kend and Nguyen, 2022). To the best of our knowledge, our study is the first that uses a large sample size and archival audit data to examine the impact on lockdown and other public health restrictions on audit processes.…”
Section: Introductionmentioning
confidence: 99%
“…Another study by Kend and Nguyen (2022) looked at the impact of COVID-19 on audit procedures for Australian companies by comparing auditors' reports in 2019 and 2020. The study results showed that large audit firms reported most COVID-19 audit procedures.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…Previous literature has shown that auditors responded to the financial crisis by increasing their effort (Xu et al , 2013;Geiger et al , 2014). Kend and Nguyen (2022) examine auditing procedures undertaken by audit firms in Australia during the initial year of the pandemic and find that some firms adopted audit procedures specially designed to address audit risk associated with the pandemic, which possibly had a positive impact on audit quality. Additionally, investors and regulators may pay close attention to financial statements due to the uncertainty brought on by the pandemic.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%